Biofilm antifungal susceptibility of Candida urine isolated from ambulatory patients - Débora da Luz Becker; Danielly Joani Bulle; Paula Lutjohann Rodrigues; Odelta Dos Santos; Daiane Flores Dalla Lana; Alexandre Meneghello Fuentefria (Universidade de Santa Cruz do Sul, 2016)
Background and Objectives: the association between the biofilm formations an antifungal resistance has been suggested to be an important factor in the pathogenesis of several Candida species. Besides, studies have included invasive candidiasis from hospitalized patients; however there are few studies that evaluated the species distribution, antifungal susceptibility and biofilm formation of Candida species isolated from ambulatory patients. Thus, the aim of this study was to evaluate whether biofilm producing contributes to antifungal resistance in Candida isolates from urine sample obtained from ambulatory patients. Methods: During one year, 25 urine samples positive for yeast were collected, stored and plated on agar supplemented with chloramphenicol and Sabouread left at room temperature for 5 days for subsequent: 52% (13/25) were C. albicans, 36% (9/25) C. tropicalis, 8% (2/25) C. krusei and 4% (1/25) C. parapsilosis. Results: The ability to form biofilm was detected in 23 (92%) of the yeast studied and 15.4% (2/13) of C. albicans were fluconazole (FLU) and ketoconazole (KET) resistant, while 11.1% (1/9) of C. tropicalis were ketoconazole resistant and were anidulafungin (ANI) non-susceptible. Conclusion: our results showed the high capacity for biofilm formation among Candida isolates from ambulatory patients.